Level of Parental Knowledge about Maintenance of Dental and Oral Hygiene in Early Childhood - Farrah F. Sumangando; Christy N. Mintjelungan; Damajanty H. C. Pangemanan (Universitas Sam Ratulangi, 2022)
Abstract: Parental knowledge is very important in shaping behavior that supports or does not support oral and dental hygiene of children. The ability of parents to maintain the dental health of their children is strongly influenced by their level of education, age, marital status, occupation, and income. This study aimed to determine the level of parental knowledge about the maintenance of dental and oral hygiene in early childhood. This was a descriptive study with a cross sectional design. Respondents were mothers of early childhood children who had complete primary teeth with an age range of 3-5 years, and domiciled in Tosuraya Village, Ratahan, Southeast Minahasa. The results obtained 32 mothers as respondents. Mothers with children aged 3 years had the highest number of 17 respondents (53.1%). Based on maternal age, respondents at the age of 26-30 years were 12 people (37.5%), and of 21-25 years were 11 people (34.4%). The most frequent occupation of respondents was housewife amounted to 24 people (75%). The most common level of education was SMA/SMK (senior high school) with a total of 21 people (65.6%). In determination of parental category based on maternal education level, the most frequent was senior high school (43.75%) followed by D3/S1 (18.75%) belonged to good category with a total of 20 respondents (62,5%). In conclusion, most parents (mothers) had good category level of knowledge about the maintenance of dental and oral hygiene in early childhood.Keywords: parental knowledge; dental and oral hygieneÂ Abstrak: Pengetahuan orang tua sangat penting dalam membentuk perilaku yang mendukung atau tidak mendukung kebersihan mulut dan gigi anak. Kemampuan orang tua dalam menjaga kesehatan gigi anak sangat dipengaruhi oleh tingkat pendidikan, usia, status pernikahan, pekerjaan, dan pendapatan. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan orang tua tentang pemeliharaan kebersihan gigi dan mulut pada anak usia dini. Jenis penelitian ialah deskriptif dengan desain potong lintang. Responden ialah ibu dari anak usia dini yang telah memiliki gigi sulung lengkap dengan rentang usia 3-5 tahun dan berdomisili di Kelurahan Tosuraya, Kecamatan Ratahan, Kabupaten Minahasa Tenggara. Hasil penelitian mendapatkan 32 orang ibu sebagai responden. Responden yang mempunyai anak usia 3 tahun ialah terbanyak dengan jumlah 17 orang (53,1%). Responden dengan usia ibu 26-30 tahun sebanyak 12 orang (37,5%), dan 21-25 tahun sebanyak 11 orang (34,4%). Pekerjaan responden sebagai ibu rumah tangga berjumlah 24 orang (75%), dan tingkat pendidikan terbanyak ialah SMA/SMK dengan jumlah 21 orang (65,6%). Pengukuran tingkat orang tua berdasarkan pendidikan ibu yang terbanyak ialah SMU/SMK (43,75%) diikuti D3/S1 (18,75%) tergolong kategori baik dengan total 20 responden (62,5%). Simpulan penelitian ini ialah tingkat pengetahuan ibu tentang pemeliharaan kebersihan gigi dan mulut pada anak usia dini sebagian besar termasuk dalam kategori baik.Kata kunci: pengetahuan orang tua; kebersihan gigi dan mulut